Mangosteen (Garcinia mangostana L.) Peel Decoction Effect on Embryological Development of Wader Pari Fish Rasbora lateristriata (Bleeker, 1854) - Khasanah, Luthfia Uswatun; Paramita, Pradnya; Retnoaji, Bambang (Journal of Tropical Biodiversity and Biotechnology, 2024)
Mangosteen (Garcinia mangostana L.) is a tropical fruit that has become a sought-after commodity by enthusiasts from various countries, including Indonesia. The active components found in mangosteen peel primarily consist of active xanthone compounds, such as mangostenol, mangostin, mangostino A, mangostino B, tvophylin B, trapezifolixanthone, alpha mangostin, beta mangostin, garcinon B, mangostano, as well as flavonoids epicatechin and gartanin. These compounds exhibit a range of beneficial properties, including anti-inflammatory, antibacterial, antifungal, antihistamine, antidiabetic, anticancer, and more. Consequently, there is significant potential in developing mangosteen peel extract as a valuable ingredient in herbal medicine. However, there is currently no available data on the effects of exposure to mangosteen peel decoction on fish animal models. Therefore, it is essential to investigate the impact of mangosteen peel decoction on wader pari fish (Rasbora lateristriata) embryos. In this study, wader pari embryos were subjected to various concentrations of mangosteen peel decoction (0.5, 1, 5, and 25 µg/mL). The effects on egg hatchability, survival rate (SR), heart rate frequency, and heart morphology of the larvae were meticulously examined using a Leica microscope. The data obtained were subjected to statistical analysis using one-way ANOVA. The findings demonstrated that exposure to mangosteen peel decoction resulted in lower hatching rates and embryonic survival, alongside an increased heart rate frequency. Additionally, the exposed embryos displayed cardiac edema and cardiac bending, particularly at the concentration of 25 µg/mL. In conclusion, the exposure of wader pari fish embryos to mangosteen peel decoction at the concentrations of 25 µg/mL and higher significantly affected the hatching rate, survival rate, and heart rate of R. lateristriata fish larvae.